Effect of Sintering Temperature on Crystal Structure and Conductivity of the CaCO3-Doped Li4Ti5O12 Anodes from Blood Clam Shells (Anadara granosa) - Marhan Ebit Saputra; Megawati Ayu Putri; Eka Febrianti; Widodo Budi Kurniawan (Universitas Ahmad Dahlan, 2022)
CaCO3-doped Li4Ti5O12 was synthesized by solid-state method with sintering temperatures at 750 °C, 800 °C, and 850 °C. The source of CaCO3 was used from blood clam shells (Anadara granosa) with a content of 97.67%. The influence of sintering temperature on crystal structure and conductivity of CaCO3-doped Li4Ti5O12 are extensively studied. XRD results show there is no CaCO3 phase found, which indicates that the doping of Li4Ti5O12 with CaCO3 has been successful. The smallest crystallite size was obtained at a sintering temperature of 800 °C, which is 46.49 nm, which is beneficial for shortening diffusion length and facilitating the electron and ion transport, causing an increase in anode conductivity. The most optimal conductivity was obtained in samples with a sintering temperature of 800 °C with a conductivity of 2.46 x 10-4 S/cm. When the sintering temperature is increased to 850 °C, the particles tend to agglomerate and deteriorate the electrochemical properties.